Photodynamic degradation of vitamin E induced by psoralens - Costantini, Claudio; d'Ischia, Marco; Napolitano, Alessandra; Misuraca, Giovanna; Prota, Giuseppe (Biochimica et biophysica acta, 1992)
Psoralens and other furocoumarins currently used in PUVA photochemotherapy are shown to have, to a variable extent, the ability to hasten the rate of ultraviolet-induced photooxidation of α-tocopherol (α-T) in ethanol or ethanol-phosphate buffer (pH 6.8). The sensitizing effect varies significantly with the substrate concentration and the nature of the furocoumarin used, and is dependent on the presence of oxygen. Scavengers of singlet oxygen, e.g., sodium azide, markedly inhibit the psoralen-sensitized photooxidation of α-T, whereas superoxide dismutase exerts an opposite, accelerating effect on the reaction rate. Catalase has no significant influence on the kinetics of α-T decay. Analysis of the products formed by psoralen-sensitized photooxidation of α-T in ethanol-phosphate buffer showed the presence of α-tocopherolquinone, its 2,3-epoxide and two related compounds containing the 7-oxaspiro[4,5]dec-1-ene-3,6-dione ring system. The nature of these products, coupled with the results of the kinetic experiments, suggest that psoralens induce a type II, oxygen-dependent photodegradation of α-T primarily mediated by singlet oxygen.